2001
DOI: 10.4049/jimmunol.166.1.293
|View full text |Cite
|
Sign up to set email alerts
|

Bi-Directional Activation Between Human Airway Smooth Muscle Cells and T Lymphocytes: Role in Induction of Altered Airway Responsiveness

Abstract: Because both T lymphocyte and airway smooth muscle (ASM) cell activation are events fundamentally implicated in the pathobiology of asthma, this study tested the hypothesis that cooperative intercellular signaling between activated T cells and ASM cells mediates proasthmatic changes in ASM responsiveness. Contrasting the lack of effect of resting human T cells, anti-CD3-activated T cells were found to adhere to the surface of naive human ASM cells, increase ASM CD25 cell surface expression, and induce increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 44 publications
(54 reference statements)
5
42
0
Order By: Relevance
“…Clearly, further research is needed into the mechanisms of AHR protection by IL-10, especially to investigate whether IL-10 directly acts on effector T cells or via APCs (39,40) and whether there are direct effects of TGF-␤1 and IL-10 on airway smooth muscle cells (ASM). Both cytokines have been shown to inhibit chemokine expression in ASM (41)(42)(43) and, in humans, adhesion of T lymphocytes to ASM has been found to increase AHR (44).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, further research is needed into the mechanisms of AHR protection by IL-10, especially to investigate whether IL-10 directly acts on effector T cells or via APCs (39,40) and whether there are direct effects of TGF-␤1 and IL-10 on airway smooth muscle cells (ASM). Both cytokines have been shown to inhibit chemokine expression in ASM (41)(42)(43) and, in humans, adhesion of T lymphocytes to ASM has been found to increase AHR (44).…”
Section: Discussionmentioning
confidence: 99%
“…Integrins (intercellular adhesion molecule-1 and vascular cell adhesion molecule-1) and CD44 are important for the adhesion of T-cells to ASM cells; adhesion between activated T-cells and ASM cells leads to DNA synthesis in the ASM cells [36]. Major histocompatibility complex (MHC) class II and the co-stimulatory molecules CD40 [37,38], CD80 and CD86 [39] are also present on ASM cells. Despite the expression of MHC class II, ASM cells are not able to present antigen [38].…”
Section: Asm Secretory Functionmentioning
confidence: 99%
“…(ICAM)-1, [17][18][19]27 whereas CD40 ligation on M⌽ triggers LFA-1 and ICAM-1 expression (Table 2 and Figure 2A). 38 Notably, stimulation with CD40L enhanced the adhesion of T lymphocytes to cultured ECs, but diminished that of neutrophils, a cell type not commonly detected within undisrupted human atheroma.…”
Section: Adhesion Of Immunocompetent Cellsmentioning
confidence: 99%
“…Although it was originally discussed controversially, several groups have subsequently confirmed the expression of CD40L on nonlymphocytic cell types (Table 1). [22][23][24][25][26][27] Both receptor and ligand, expressed on cultured ECs, SMCs, and M⌽, are functional, mediating the various proatherogenic processes outlined below (Table 2). In additional studies, our group demonstrated expression of CD40 and CD40L in atheromatous tissue of hypercholesterolemic mice with a staining pattern similar to that observed in humans.…”
Section: Expression Of Cd40 and Cd40l In Human Atheroma-associated Cellsmentioning
confidence: 99%